Collingwood on Philosophical Methodology (Philosophers in Depth, 2018)
This book investigates the contribution of R.G. Collingwood to the field of philosophical methodology through a discussion of Collingwood's conception of the role and character of philosophical analysis. It explores questions, such as, is there anything distinctive about the activity of philosophizing? If so, what distinguishes philosophy from other forms of inquiry? What is the relation between philosophy and science and between philosophy and history? For much of the twentieth century, philosophers philosophized with little self-awareness; Collingwood was exceptional in the attention he paid to the activity of philosophizing. This book will be of interest both to those who are interested in Collingwood's philosophy and, more generally, to all who are interested in the question 'what is philosophy?'.